2020
DOI: 10.48550/arxiv.2009.02750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compact steep-spectrum and peaked-spectrum radio sources

Christopher P. O'Dea,
D. J. Saikia

Abstract: Compact steep-spectrum (CSS) and peaked spectrum (PS) radio sources are compact, powerful radio sources. The multi-frequency observational properties and current theories are reviewed with emphasis on developments since the earlier review of O'Dea (1998). There are three main hypotheses for the nature of PS and CSS sources. (1) The PS sources might be very young radio galaxies which will evolve into CSS sources on their way to becoming large radio galaxies. (2) The PS and CSS sources might be compact because t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 488 publications
(896 reference statements)
3
11
0
Order By: Relevance
“…The evolution model where compact radio lobes expand and become large FR Is and FR IIs are well consistent with radio observational data (e.g., Kawakatu et al 2008;Kunert-Bajraszewska et al 2010;O'Dea & Saikia 2020). Kawakatu et al (2008) studied the properties of more than 100 radio lobes and by comparing the hot spot advancing speed with the sound speed of the ambient medium, they indicated that only compact symmetric objects whose initial advance speed is faster than about 0.1 c can evolve into FR II class.…”
Section: New Pathway For Fr I/fr II Dividesupporting
confidence: 77%
“…The evolution model where compact radio lobes expand and become large FR Is and FR IIs are well consistent with radio observational data (e.g., Kawakatu et al 2008;Kunert-Bajraszewska et al 2010;O'Dea & Saikia 2020). Kawakatu et al (2008) studied the properties of more than 100 radio lobes and by comparing the hot spot advancing speed with the sound speed of the ambient medium, they indicated that only compact symmetric objects whose initial advance speed is faster than about 0.1 c can evolve into FR II class.…”
Section: New Pathway For Fr I/fr II Dividesupporting
confidence: 77%
“…The radio characteristics of many sources are consistent with powerful (26.8 < log(L 1.4 GHz /W Hz −1 ) < 28), sub-galactic, and high pressure (log(P 10 GHz /dyne cm −3 ) > −7) radio sources typical of those seen in compact and young radio AGN (e.g., Readhead et al 1996;Orienti & Dallacasa 2014). The radio sources in our sample are therefore similar to other well-known classes of young and compact radio sources: the Compact Steep Spectrum (CSS) sources, Gigahertz-Peaked Spectrum (GPS) sources, and High-Frequency Peakers (HFP) (see reviews by O'Dea 1998;O'Dea & Saikia 2020).…”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, it can explain the global properties of the GPS/CSS population, e.g., the observed linear size vs. turnover relation (O'Dea & Baum 1997) and provides magnetic field estimates consistent with the equipartition fields estimated from the optically thin part of the spectrum (Orienti & Dallacasa 2008a). The consensus, then, is that SSA will always be present to some degree in radio-emitting plasma (Fanti 2009;Orienti 2016;O'Dea & Saikia 2020). In what follows we continue to assume that the peaked spectra result from SSA.…”
Section: Synchrotron Self-absorption (Ssa)mentioning
confidence: 80%
“…The relativistic jets of NLS1s are usually rather compact (Gu et al 2015;Berton 2018;Liao & Gu 2020;Chen et al 2020), although some exceptions are known (e.g., Gliozzi et al 2010;Richards & Lister 2015;Congiu et al 2017a;Rakshit et al 2018;Gabányi et al 2018;Congiu et al 2020). This has led some authors to suggest that NLS1s may be connected with classes of young radio galaxies such as compact steep-spectrum (CSS) sources and gigahertz-peaked sources (GPS) (Oshlack et al 2001;Gallo 2006;Komossa et al 2008;Caccianiga et al 2014;Berton et al 2017;Caccianiga et al 2017;Liao & Gu 2020;O'Dea & Saikia 2020;Yao & Komossa 2020). Indeed, several radio galaxies show signs of line shifts and broadening induced by the presence of jets (Tadhunter et al 2001;Marziani et al 2003;Holt et al 2006;Venturi et al 2020), and this seems particularly common in young radio galaxies, where the jet is directly interacting with the ISM (Morganti et al 2015;Orienti 2016).…”
Section: Origin Of the Bulk Outflowsmentioning
confidence: 99%